PENERAPAN MEDIA PEMBELAJARAN BERBASIS MACROMEDIA FLASH UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN ALAT DAN MESIN PERTANIAN KELAS X ATP DI SMK NEGERI 7 MAJENE - Eka Putri; Husain Syam; Muhammad Rais (Universitas Negeri Makassar, 2018)
This study is a classroom action research that aims to improve students' motivation and learning outcomes on the subjects of agricultural tools and agricultural machines class X agricultural agribusiness skills program (ATP) SMK Negeri 7 Majene with the use of macromedia flash based learning media. The subjects of this study are the students of class X ATP 2 SMK Negeri 7 Majene in the odd semester of academic year 2017/2018 consisting of 33 students. This research was conducted in two cycles consisting of four activities, namely: planning, implementation, observation/observation, and reflection. Data collection of motivation and learning outcomes, as well as activities of student learning activities is done by using observation sheet and test result sheet in cycle I and cycle II. The collected data is analyzed quantitatively and qualitatively. Based on the results of research, it can be concluded that the use of media based learning macromedia flash can improve motivation and learning outcomes of students of class X ATP SMK Negeri 7 Majene.